Cultural Changes at Korean Tennis Clubs Due to COVID-19 : Focusing on the Accepted Culture - Min-Cheul Kim; Hanbeom Kim (Korea Institute of Sport Science, 2023)
PURPOSE This study examined the cultural experiences of tennis club members that have changed due to COVID-19, specifically emphasizing the accepted culture within these clubs. METHODS Seven tennis club members, with over five years of experience, active participation in two or more clubs, and a history of active participation, were interviewed using in-depth interviews and a semi-structured questionnaire. RESULTS Firstly, the tennis club members accepted the "no contact" culture that has emerged since COVID-19. Secondly, social distancing made getting together in large groups difficult, and tennis club activities became more limited. This has led to weakening the tennis club community, which is different from what we have seen before. Lastly, the growing interest in non-traditional content has led to an increase in participants enjoying tennis through social media. The information and experiences gained through social media have changed the perception of coaching. CONCLUSIONS The cultures that tennis players have adopted due to COVID-19 are expected to continue in the future. The findings from this study may provide evidence for understanding the changing culture of sports in the future.